A Long Weekend in Pest and Buda - Makk, Karoly; Ragalyi, Elemér; Töröcsik, Mari; Darvas, Ivan; Nagy-Kálózy, Eszter (Second Run, 2006)
"A Long Weekend in Pest and Buda" came about partly because of a suggestion by Marc Vlessing, the film’s eventual producer, that Makk ought to make a film which looked at the recent past in Hungary. At the time (1997), Vlessing and Makk were in London putting the finishing touches to "The Gambler"; as the date suggests, the film had had a long gestation period, partly due to the usual problems of finding financial backing, not easy for a film made in Hungary, with Hungarian personnel, actors (with one exception), and a distinctly Hungarian theme and topic. From early on in the development of the project, Makk was keen to include the two actors from "Love", Iván Darvas and Mari Törőcsik, despite any notions this may have raised about the film being a continuation or even a remake of the earlier film. The story of Iván and his former lover Mari, as they struggle to come to terms with the past, also becomes the story of his generation. [www.dvdbeaver.com]